DDRE-17. INITIAL CLINICAL EXPERIENCE USING OSIMERTINIB IN PATIENTS WITH RECURRENT MALIGNANT GLIOMAS WITH EGFR ALTERATIONS. (9th November 2020) - Abousaud, Marin; Faroqui, Naqeeb; Hsu, Fang-Chi; Lesser, Glenn; Strowd, Roy; Ramkissoon, Shakti; Kwatra, Madan; Houston, Kristin Strickland; Carter, Annette; DeTroye, Alisha
Abstract: EGFR alterations are commonly observed in malignant gliomas (MG), especially glioblastomas, making this pathway an appealing therapeutic target. Unlike other EGFR tyrosine kinase inhibitors (TKIs), osimertinib (osi), a third-generation, irreversible EGFR-TKI commonly used to treat EGFR-mutant lung cancer, is able to effectively penetrate the blood brain barrier (BBB) and achieve therapeutic concentrations in brain tissue. METHODS: A retrospective chart review identified six patients (pts) aged 46–74 years with recurrent MG and known EGFR alterations identified by next generation sequencing who received at least one dose of osi between 1/1/2018 and 5/26/2020. Patients received osi 80 mg by mouth once daily and continued treatment until disease progression, the development of unacceptable side effects, medical complications, or death. RESULTS: All patients had EGFR amplification. Other EGFR alterations identified included EGFRvIII (1 pt), deletion of introns 1–7 (3 pts) and deletion of introns 13–15 (2 pts). Four of the six patients were evaluable for response. Three patients (75.0%) had stable disease (SD) as best response and one patient (25.0%) was refractory to treatment. One patient with an EGFRvIII mutation achieved stable disease on osi and remained on treatment for 236 days. Thrombocytopenia developed in 2 patients (grade 2 (1), grade 3 (1) in patient also on concurrent bevacizumab) and 1 patient developed grade 1 diarrhea and pneumonia. Overall, this heavily pretreated patient population tolerated osi therapy and half of the patients had a best response of SD which lasted from 77 to 236 days. CONCLUSIONS: Osi has a tolerable safety profile in this heavily pretreated brain tumor population, and it may benefit selected patients with recurrent MG containing EGFR alterations. Further clinical investigations are needed, particularly in patients whose tumors express an EGFRvIII mutation, to identify which EGFR alterations may sensitize tumors to this BBB penetrant EGFR-TKI.